Generalized rational $ α_{*}- $ contraction in $ C^{*}- $algebra-valued b-metric spaces (Jurnal Matematika, Statistika dan Komputasi, 2022)
This present paper extends some common fixed point theorems for generalized rational $ α_{*}- $ contraction of multi-valued mappings in the setting of $ C^{*}- $algebra-valued b-metric spaces .
Keywords: Fixed point; generalized rational $ α_{*}- $ contraction; multi-valued mapping; Picard sequences; C^{*}- $algebra-valued b-metric spaces